Security Policies of India, Brazil and South Africa – Regional Security Contexts as Constraints for a Common Agenda - Daniel Flemes; Alcides Costa Vaz (German Institute of Global and Area Studies (GIGA), 2011)
In the course of the last decade, the IBSA states (India, Brazil, South Africa) have increased their weight in the shifting global order, particularly in economic affairs. Can the same be said about the IBSA states' position in the international security hierarchy? After locating the IBSA coalition in the shifting world order, we analyze its member states' willingness and capacity to coordinate their security policies and build a common global security agenda. In addition, we explore the state of and perspectives on bi- and trilateral collaboration initiatives on defense and armaments between India, Brazil and South Africa. A key reason for the mostly modest results of global security agenda coordination and cross-regional defense collaboration is that the prevailing security concerns of each country are located at the regional level. Therefore, the starting point of an assessment of the prospects of IBSA's security cooperation and its potential impact on the strategic global landscape has to be a comparative evaluation of the regional security environments, focusing on overlaps and potential synergies between the national security policies of the three state actors. – – Im Verlauf der letzten Dekade konnten die IBSA-Staaten (Indien, Brasilien, Südafrika) ihre Position in der sich verschiebenden Weltordnung erheblich verbessern; das gilt insbesondere für ihren Einfluss auf globale Handelsfragen. Lässt sich ein ähnlicher Aufstieg der IBSA-Staaten in der internationalen Sicherheitsordnung konstatieren? Die Autoren verorten die IBSA-Koalition in der sich verschiebenden Weltordnung und analysieren die Bereitschaft und Fähigkeit der drei Staaten, ihre Sicherheitsstrategien zu koordinieren und eine gemeinsame Sicherheitsagenda zu entwerfen. Ferner werden die Bedingungen und Perspektiven biund trilateraler Verteidigungs- und Rüstungszusammenarbeit untersucht. Im Ergebnis zeichnen sich bisher allenfalls anfängliche Bemühungen bei der Zusammenarbeit im Verteidigungssektor und bei der Entwicklung einer globalen Sicherheitsagenda ab. Ausschlaggebend dafür sind die primär auf der regionalen Ebene liegenden Sicherheitsprioritäten der IBSA-Staaten. Die perspektivische Bewertung des potenziellen Einflusses der Staatenkoalition auf globale Sicherheitsfragen erfolgt demnach vor dem Hintergrund der regionalen Sicherheitsstrategien Indiens, Brasiliens und Südafrikas. Dabei stehen mögliche Überschneidungen und Synergien zwischen den regionalen Sicherheitsstrategien im Zentrum des Interesses.
Keywords: 300; India; Brazil; South Africa; IBSA Dialogue Forum; security policies; security context; military power; Politischer Konflikt; Bündnissystem; Großmacht; Militärpotenzial; Internationale Beziehungen; Außenwirtschaftspolitik; Indien; Brasilien; Südafrika